Dapagliflozin in type 2 diabetes: effectiveness across the spectrum of disease and over time. Issue 2 (28th November 2014) - Parikh, S.; Wilding, J.; Jabbour, S.; Hardy, E.
Summary Background Despite many available therapies, patients with type 2 diabetes mellitus (T2DM) frequently do not achieve/maintain glycaemic control. Furthermore, side effects such as hypoglycaemia and weight gain may limit therapy choices. Dapagliflozin, a selective sodium‐glucose cotransporter‐2 inhibitor, reduces hyperglycaemia by increasing glucosuria independently of insulin, representing a novel approach in T2DM. Dapagliflozin efficacy, safety and tolerability were evaluated across a wide range of clinical trials. Methods Dapagliflozin 10‐mg efficacy data from (i) two short‐term, active‐comparator studies (vs. metformin‐XR over 24 weeks and vs. glipizide over 52 weeks), (ii) pooled 24‐week analyses of five placebo‐controlled trials (as monotherapy or add‐on therapy), and (iii) long‐term studies over 2 years; dapagliflozin 5‐ and 10‐mg pooled safety data from 12 placebo‐controlled trials; and cardiovascular safety and malignancy data from 19 dapagliflozin studies were evaluated. Results In treatment‐naïve patients (baseline HbA1c 9%), dapagliflozin reduced HbA1c (−1.45%) similarly to metformin‐XR (−1.44%). In metformin‐treated patients (baseline HbA1c 7.7%), dapagliflozin achieved a clinically significant reduction (−0.52%) similar to glipizide (−0.52%). In pooled 24‐week analyses, dapagliflozin vs. placebo differences in HbA1c, weight and systolic blood pressure (SBP) were −0.60%, −1.61 kg and −3.6 mmHg, respectively. At 2 years, dapagliflozin vs. placebo differences in HbA1c and weight were −0.44 to −0.80% and −2.41 to −3.19 kg, respectively, and vs. glipizide, differences in HbA1c, weight, and SBP were −0.18%, −5.06 kg, and −3.89 mmHg, respectively. Major hypoglycaemia with dapagliflozin was rare (< 0.1%). Urinary tract and genital infections were more common with dapagliflozin, but responded to standard care and rarely led to study discontinuation. Events of renal failure/impairment and malignancies were rare and balanced across treatment groups. Pooled analyses did not indicate that dapagliflozin increased cardiovascular event risk. Conclusions Dapagliflozin improved glycaemic control, decreased body weight, and lowered blood pressure across the spectrum of T2DM disease, with maintenance of these benefits over time.